Urgensi Pembelajaran Bahasa Arab bagi Hafizhul Qur’an - Alpan Noor Habib Rangkuti; Hanifah Khairiyah; Sri Yulia Yuliani; Winda Maghfira Yuliana (Muhadasah: Jurnal Pendidikan Bahasa Arab, 2022)
Abstract. Arabic and the Qur'an are two interrelated things, because Arabic is used as the language in the Qur'an. Learning Arabic is not only an existing subject, but also a worship that can be done, because Arabic is the main requirement in reading the Qur'an. In addition to reading, humans are required to memorize, understand, and practice what is contained in the Qur'an. Of course, to do these four things requires mastery of the language used, namely Arabic. The purpose of this article is to examine whether there is an urgency in learning Arabic for hafizhul Qur'an. The type of research used is descriptive analysis research, with a qualitative approach. The data collection technique used is the interview technique, where the sample interviewed is the memorizer of the Qur'an. From the interviews that have been conducted, the authors get a correlation or relationship between learning the Qur'an and memorizing the Qur'an. So, based on the results of interviews and various journal references, there is an urgency in learning Arabic for hafizhul Qur'an.